2013
DOI: 10.1016/j.ijscr.2013.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum, a pathogen in documented cholecystitis

Abstract: While the routine use lactobacillus species as a probiotic is supported in the literature, understanding its potential role as a pathogen may allow more judicious use of these bacteria and encourage research to elucidate the pathogenicity of lactobacillus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…is rare; bile fluid is typically infected with Escherichia coli, Enterococcus spp., Klebsiella spp., Enterobacter spp., Clostridium spp., and Bacteroides fragilis group [6]. To the best of our knowledge, there are only four other case reports worldwide thus far reporting primary pathogenic Lactobacillus in the setting of acute cholecystitis, only two of which are from within the United States and only one of which was complicated with peritonitis just like our patient's case [7][8][9][10].…”
Section: Discussionmentioning
confidence: 45%
“…is rare; bile fluid is typically infected with Escherichia coli, Enterococcus spp., Klebsiella spp., Enterobacter spp., Clostridium spp., and Bacteroides fragilis group [6]. To the best of our knowledge, there are only four other case reports worldwide thus far reporting primary pathogenic Lactobacillus in the setting of acute cholecystitis, only two of which are from within the United States and only one of which was complicated with peritonitis just like our patient's case [7][8][9][10].…”
Section: Discussionmentioning
confidence: 45%
“…A PubMed and ClinicalKey review of the literature identified six cases (out of eight reported cases of Lactobacillus liver abscess) that occurred in diabetics. However, each of those reported cases had an additional underlying disease process, particularly involving the hepatobiliary system such as post-cholecystectomy, ERCP, cholangitis, and Mirizzi syndrome, or other intestinal pathology including Crohn's disease [10,12,14,16,17]. Our patient only had uncontrolled diabetes thus predisposing him to increased risk of endothelial injury and bacterial translocation.…”
Section: Discussionmentioning
confidence: 84%
“…Other case reports (Appendix; Table 2) have identified probiotics as the etiology for the development of Lactobacillus liver abscess [9,17]. The use of probiotics has become widespread over the past few decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This illustrates the ability of microorganisms, even those considered harmless, to colonise patients suffering from life‐threatening illnesses. Out of the rest, single reports associated L. paracasei (Franko et al., ), L. fermentum (Chery et al., ), L. acidophilus (Mehta et al., ), L. gasseri (Sun et al., ) and L. casei (Aroutcheva et al., ) with production of endocarditis, cholecystitis, septicaemia, surgical wound/urinary tract infection and contamination of a central catheter, respectively, in patients who have suffered from prostate cancer, coronary disease, lymphoma, simultaneous infection by a coagulase‐negative Staphylococcus and chronic lung and renal insufficiency.…”
Section: Assessmentmentioning
confidence: 99%